RESPONSE OF THE ADULT FEMALE RATS TO OVARIECTOMY AS DETERMINED BY LUTEINISING HORMONE RADIOIMMUNOASSAY - Khan, Umar Ali; Khan, Mansoor Ali; Khan, Aamir Ali (Journal of Ayub Medical College Abbottabad, 1998)
This study was carried out to see the response of ovariectomy in adult female rats as determined by rat Luteinising Hormone (rLH) Radioimmunoassay (R1A). Animals were divided in two groups. Group I (control, n=6) were sham ovariectomised and group II (experimented, n=4) were ovariectomised. Next day at 1400 hours’ rats were sacrificed and their plasma was collected for rLH, RIA. It was observed that there was highly significant increase in plasma rLH (P<0.001) in experimental group as compared to controls. Also the increase in the weights of hypothalamus and anterior pituitary of experimental group was highly significant (P<0.001) as compared to controls. This shows that this rise in plasma rLH and weights of hypothalamus and anterior pituitary was due to loss of negative feedback effect of ovarian steroids.